2006
DOI: 10.4081/ijas.2006.155
|View full text |Cite
|
Sign up to set email alerts
|

The replacement of fish oil with refined coconut oil in the diet of large rainbow trout (Oncorhynchus mykiss)

Abstract: Three hundred rainbow trout (242.9 ± 6.9 g) were randomly assigned to 12 fibreglass tanks (25 fish/tank). The fish were fed, for 231 days (feeding level: 0.74 % average bw), four experimental diets, containing increasing levels of coconut oil: diet A 0 %, diet B 6 %; diet C 12 % and diet D 13 %, as replacements of herring oil and cod liver oil. Weight gains of fish were > 3 g d-1 and FCR lower than 1.5, for all treatments. No significant difference was observed in the main car- cass traits and whole bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
6
15
0
Order By: Relevance
“…These findings are in agreement with previous investigations of CO [40], PO [41,42], and LO [43], as well as the well-established paradigm of compositional plasticity of fish tissues with respect to FA profile. Finishing augments fillet nutritional quality among fishes raised on feeds containing FO alternatives [26][27][28][29][30][31][32][33][34]; however, complete restoration of FO-associated FA profile, specifically LC-PUFA content, is rarely observed [31][32][33][34].…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in agreement with previous investigations of CO [40], PO [41,42], and LO [43], as well as the well-established paradigm of compositional plasticity of fish tissues with respect to FA profile. Finishing augments fillet nutritional quality among fishes raised on feeds containing FO alternatives [26][27][28][29][30][31][32][33][34]; however, complete restoration of FO-associated FA profile, specifically LC-PUFA content, is rarely observed [31][32][33][34].…”
Section: Discussionsupporting
confidence: 94%
“…The lipid quality indexes were similar to those reported by Poli et al (2003) for the meagre and by Rondan et al (2004) and Ballestrazzi et al (2006) for other fish species and to those of other foodstuffs which are advisable for human consumption (Peres-Llamas et al, 1998).…”
Section: Resultssupporting
confidence: 88%
“…However, for group A, the incidence of the fillet fat was very low as well, confirming that the name meagre of this species is perfectly appropriate. The raised meagre showed fat contents (about 3%) of fillets not very different from those of the wild caught fish and, from this point of view, is very different from the other species (in particular sea bass, gilthead sea bream and trout), in which higher percentages of fat (from 2 to 5 times) occur (Orban et al, 1996;Lanari et al, 1999;Orban et al, 1999;Poli et al, 2001;Ballestrazzi et al, 2006). The low incidence of fat in the fillet of group A, fed a diet at 20.7% of fat, suggests that the use of diets with a progressive increase in fat levels is possible without wors- Confirming what has already been stated, the protein content was similar for both groups (21.09 and 20.89%, respectively for groups A and B).…”
Section: Resultsmentioning
confidence: 95%
“…The reasons for the differences between fed and retained fatty acid levels are unclear as trout appear to have limited ability to elongate and desaturate dietary fatty acids into DHA (Hardy 2002). Other researchers have reported similar results with similar fatty acid sources (Ballestrazzi et al 2006).…”
Section: Discussionsupporting
confidence: 80%
“…Medium chain‐length saturated fatty acids supplied through coconut oil (43% lauric acid) have been shown to be viable energy sources for many fish species including red drum, Sciaenops ocellatus; African catfish, Heterobranchus lonifilis ; and common carp, Cyprinus carpio L. (Craig and Gatlin 1995; Legendre et al 1995; Fontagné et al 1999). More recently, Ballestrazzi et al (2006) reported that rainbow trout fed up to 13% coconut oil as a replacement for fish oil maintain growth performance when fish meal levels were maintained at 23%. Olsen et al (1998) reported that, in Arctic charr, Salvelinus alpinus , the lauric acid present in coconut oil was more efficiently absorbed than other longer saturated fatty acids in the pyloric caeca and gut.…”
Section: Discussionmentioning
confidence: 99%